A microswitch-aided program to enable people with extensive multiple disabilities to control environmental stimulation through different responses - Lancioni, Giulio E.; Singh, Nirbhay N.; O'Reilly, Mark F.; Sigafoos, Jeff; Alberti, Gloria; Chiariello, Valeria; Desideri, Lorenzo (Frontiers in Psychiatry, 2022)
Objectives: This study assessed whether a simple technology-aided program (i.e., a program involving the use of microswitches linked to a smartphone) could be set up to enable people with motor, sensory and intellectual disabilities to control preferred environmental stimulation through two different response movements. Methods: Ten participants were involved in the study. Each of them was exposed to an ABAB design, in which A represented baseline phases without the program and B intervention phases with the use of the program. The study assessed whether the participants (a) had significant increases of each of the two response movements available and/or showed response variability across sessions and over time and (b) had signs of satisfaction/happiness during the study sessions, in connection with their stimulation access and control. Results: The program was effective in increasing the participants’ responding and consequently their self-regulated stimulation input. Half of the participants showed a significant increase of both responses available from the first intervention phase. Other participants seemed to focus more on one of the two responses. Even so, they tended to have occasionally high performance frequencies also with regard to their non-dominant (not significantly increased) response. Finally, all participants showed clear signs of satisfaction/happiness during the intervention sessions. Conclusions: The program represents a potentially useful approach for enabling people with extensive multiple disabilities to self-regulate their access to preferred environmental stimulation and improve their mood.